2013
DOI: 10.4028/www.scientific.net/amr.802.129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N Incorporation on Growth Behavior of InGaAsN/GaAs/Ge Multi-Layered Structure by MOVPE

Abstract: We have investigated an effect of N incorporation on InGaAsN on Ge (001), which is proposed to be a part of the InGaP(N)/InGaAs/InGaAsN/Ge four-junction solar cell, and on its growth behavior. Results obtained from high resolution X-ray diffraction and Raman scattering demonstrated that high quality In0.11Ga0.89As1-yNy films with N (y) contents up to 5% were successfully grown on n-type doped Ge (001) substrate by metalorganic vapor phase epitaxy using low-temperature (500°C) GaAs buffer layer. As expectation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…2(b) with the g-vector of (a) = ( 002 surface. Therefore, it is possible to form APBs, which consist of Ga-Ga or As-As bonds along the [001] direction as shown in the model reported in the previous work [8]. Moreover, we cannot prove the APDs structure in all micrographs because ultrathin of the TEM specimen thickness and low specimen tilt angle are needed.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…2(b) with the g-vector of (a) = ( 002 surface. Therefore, it is possible to form APBs, which consist of Ga-Ga or As-As bonds along the [001] direction as shown in the model reported in the previous work [8]. Moreover, we cannot prove the APDs structure in all micrographs because ultrathin of the TEM specimen thickness and low specimen tilt angle are needed.…”
Section: Resultsmentioning
confidence: 93%
“…However, I. Németh et al [4] reported the optimization of dark field TEM imaging condition for the detection of APDs structure in GaP film grown on Si substrate. In the previous work, we have investigated In 0.11 Ga 0.89 As 1-y N y films with N (y) contents up to 5% grown on n-type doped Ge (001) substrate [5]. When the N content in the InGaAsN grown films is increased the surface domains, which are related to APBs, become less orientation showing a larger size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, an InGaP/InGaAs/InGaAsN/Ge four-junction solar cell with a lattice-matched InGaAsN absorber layer is expected to have a conversion efficiency of over 40% [5,6]. The difficulty of the epitaxial growth of InGaAsN on Ge, which respectively are polar and non-polar semiconductors, is to prevent the formation of APDs [7,8]. Therefore, a GaAs buffer layer is required to obtain a high quality InGaAsN layer on a Ge substrate as well as to create an n-type or a p-type junction to the Ge substrate [9].…”
Section: Introductionmentioning
confidence: 99%